(Dis)honest Politicians and the Value of Transparency for Campaign Promises - Matthias Lang; Simeon Andreas Dermot Schudy (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Promises are prevalent in many competitive environments, but promise keeping is often difficult to observe. Do promises still offer an opportunity to honor future obligations, if promise keeping is unobservable? Focusing on campaign promises, we study the value of transparency. We show how preferences for truth-telling shape promise competition when promise keeping can(not) be observed. We identify the causal effects of transparency in a laboratory experiment. Transparency leads to less generous promises, but also to less promise breaking. Nonetheless, officials appropriate similar rents as in opaque institutions. Preferences for truth-telling and (instrumental) reputational concerns explain these results.
Keywords: C91; C92; D72; D73; D91; 330; prospective voting; retrospective voting; promises; promise breaking; lying costs; preferences for truth-telling; experiment; political economy